2010
DOI: 10.1074/jbc.m109.042424
|View full text |Cite
|
Sign up to set email alerts
|

The Lysyl Oxidases LOX and LOXL2 Are Necessary and Sufficient to Repress E-cadherin in Hypoxia

Abstract: Hypoxia has been shown to promote tumor metastasis and lead to therapy resistance. Recent work has demonstrated that hypoxia represses E-cadherin expression, a hallmark of epithelial to mesenchymal transition, which is believed to amplify tumor aggressiveness. The molecular mechanism of E-cadherin repression is unknown, yet lysyl oxidases have been implicated to be involved. Gene expression of lysyl oxidase (LOX) and the related LOX-like 2 (LOXL2) is strongly induced by hypoxia. In addition to the previously d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
174
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(189 citation statements)
references
References 68 publications
11
174
1
Order By: Relevance
“…Our studies demonstrate that miR-199a suppresses LOX expression in ovarian cancer cells. LOX is induced by HIF-1, cross-links collagens, and facilitates tumor metastasis (7,22,23). Hypoxia affects modification of collagens and metastasis of sarcomas (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our studies demonstrate that miR-199a suppresses LOX expression in ovarian cancer cells. LOX is induced by HIF-1, cross-links collagens, and facilitates tumor metastasis (7,22,23). Hypoxia affects modification of collagens and metastasis of sarcomas (24).…”
Section: Discussionmentioning
confidence: 99%
“…LOX cross-links collagens and is induced by HIF-1α. Moreover, LOX affects tumor cell migration and metastasis (7,11). miR-199a transfection abrogated LOX expression under hypoxia (Fig.…”
Section: Mir-199a Inhibits Peritoneal Seeding and Growth Of Ovarian Tmentioning
confidence: 93%
See 1 more Smart Citation
“…Erler et al indentified LOX as a target of HIF-1α and showed LOX-mediated hypoxia induced invasion through cell-ECM adhesion and activation (Erler et al, 2006). LOX has been shown to mediate an induction of Epithelialmesenchymal transition, owing to LOX being the target of HIF-1α (Schietke et al, 2010). Moreover, in addition to establishing HIF-1α-dependent LOX action on tumor, LOX could upregulate HIF-1α protein expression in a manner requiring LOX-mediated hydrogen peroxide production in colorectal adenocarcinoma cells (Pez et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, EMT inductors, such as hypoxia and TGFβ, promote Loxl2 gene expression [176,177], and the LOXL2 protein, in turn, interacts and stabilizes the SNAIL1 transcription factor to repress epithelial-specific gene promoters [176,177].…”
Section: Loxl2 and Cellular Differentiationmentioning
confidence: 99%